Time Between an Emergency Department Visit and Initiation of Physical Therapist Intervention: Health Care Utilization and Costs. Issue 10 (1st June 2020) - Magel, John; Kim, Jaewhan; Fritz, Julie M; Freburger, Janet K
Abstract: Objective: The aim of this study was to examine the association between the length of time between an emergency department (ED) visit and the subsequent initiation of physical therapist intervention for low back pain (LBP) on 1-year LBP-related health care utilization (ie, surgery, advanced imaging, injections, long-term opioid use, ED visits) and costs. Methods: This retrospective cohort study focused on individuals who consulted the ED for an initial visit for LBP. Claims from a single statewide, all-payers database were used. LBP-related health care use and costs for the 12 months after the ED visit were extracted. Poisson and general linear models weighted with inverse probability treatment weights were used to compare the outcomes of patients who attended physical therapy early or delayed after the ED visit. Results: Compared with the delayed physical therapy group (n = 94), the early physical therapy group (n = 171) had a lower risk of receiving lumbar surgery (relative risk [RR] = 0.47, 95% CI = 0.26–0.86) and advanced imaging (RR = 0.72, 95% CI = 0.55–0.95), and they were less likely to have long-term opioid use (RR = 0.45, 95% CI = 0.28–0.76). The early physical therapy group incurred lower costs (mean = 3, 806, 95% CI = 1, 998–4, 184) than those in the delayed physical therapy group (mean = 8, 689, 95% CI = 4, 653–12, 727). Conclusion: Early physical therapy following an ED visit was associated with a reduced risk of using some types of health care and reduced health care costs in the 12 months following the ED visit. Impact Statement: The ED is an entry point into the health care system for patients with LBP. Until now, the impact of the length of time between an ED visit and physical therapy for LBP has not been well understood. This study shows that swift initiation of physical therapy following an ED visit for LBP is associated with lower LBP-related health utilization for some important outcomes and lower LBP-related health care costs.